Chemoresistance in human ovarian cancer: the role of apoptotic regulators - Thompson Winston E; Yan Xiaojuan; Jahani-Asl Arezu; Leung Brendan; Fraser Michael; Tsang Benjamin K (BMC, 2003)
Abstract Ovarian cancer is among the most lethal of all malignancies in women. While chemotherapy is the preferred treatment modality, chemoresistance severely limits treatment success. Recent evidence suggests that deregulation of key pro- and anti-apoptotic pathways is a key factor in the onset and maintenance of chemoresistance. Furthermore, the discovery of novel interactions between these pathways suggests that chemoresistance may be multi-factorial. Ultimately, the decision of the cancer cell to live or die in response to a chemotherapeutic agent is a consequence of the overall apoptotic capacity of that cell. In this review, we discuss the biochemical pathways believed to promote cell survival and how they modulate chemosensitivity. We then conclude with some new research directions by which the fundamental mechanisms of chemoresistance can be elucidated.